Effects of Cobalt Sources and Levels on Growth Performance, Serum Biochemistry, Metabolic Activities, and Cobalt Contents in the Tissue of Juvenile Litopenaeus vannamei. (27th April 2022) - Li, Xuehe; Lin, Huaxing; Zhu, Zhanhao; Watson Ray, Gyan; Zhou, Shuangyan; Yang, Qihui; Tan, Beiping
Abstract: This two‐factorial study was designed to evaluate the influence of cobalt (Co) sources (cobalt chloride hexahydrate [Cl‐Co] and methionine Co [M‐Co]) and levels (a control and two sets of five Co diets) on the growth performance, serum biochemistry, metabolic activities, and Co contents in the tissue of juvenile Pacific white shrimp Litopenaeus vannamei . A total of 1, 320 juvenile shrimp (0.49 ± 0.01 g [mean ± SD]) were randomized into 11 groups (three replicates of each group) and reared for 8 weeks. The results showed that final body weight, weight gain rate, and specific growth rate were significantly affected by Co level, Co source, and their interaction. Different dietary sources and Co levels had significant interaction effects on the triglyceride, total protein, and cholesterol contents but not on the glucose content. The results showed that Co sources and levels had interaction effects on the activities of alanine transaminase, aspartate transaminase, and lactate dehydrogenase in serum. The interaction had a notable influence on the Co content of the muscle and hepatopancreas. The Co content increased significantly with increased Co recruitment, and the value for the M‐Co group was higher than that for the Cl‐Co group when the dietary Co level was 40 mg/kg. According to the weight gain rate, the optimal requirements of M‐Co and Cl‐Co through broken‐line regression analysis for juvenile Pacific white shrimp were 6.10 and 37.64 mg Co/kg, respectively. The growth promotion effect of M‐Co on juvenile Pacific white shrimp was higher than that of Cl‐Co.